Improving access to appropriate case management for common childhood illnesses in hard-to-reach areas of Abia State, Nigeria - Chinwoke Isiguzo; Samantha Herrera; Joy Ufere; Ugo Enebeli; Chukwuemeka Oluoha; Jennifer Anyanti; Debra Prosnitz (Journal of Global Health Reports)
# Background